PENGARUH KUALITAS PELAYANAN DAN TARIF TERHADAP KEPUASAN PELANGGAN SERTA DAMPAKNYA PADA LOYALITAS PADA PT DELTA WARAS WISATA (Dallas Tour & Travel) KOTA JAKARTA - Bactiar Rahmat, Dimas; Arianto, Nurmin (Journal of Research and Publication Innovation, 2024)
Dallas Tour & Travel as a company operating in the field of Umrah travel services has provided various kinds of Umrah travel packages that are required to pay attention to satisfaction and loyalty. The purpose of this research is to determine the influence of service quality, tariffs and satisfaction whether it has a direct influence or not on loyalty. The research method uses regression analysis and path analysis with a sample size of 100. The research results show that customer satisfaction is positively and significantly influenced by quality. Service, with a t value of 6,200 with a Sig value. 0.000 < 0.05 Rates have a positive and significant effect on satisfaction, as evidenced by the t value equal to 3.226 and a significance value of 0.002 < 0.05. This shows that 3.226 > 1.660. Satisfaction has a direct influence simultaneously F count 145.556 > F table 3.099 and 0.000 < 0.05. Service Quality has a t value of 2.084 > 1.660 and Sig 0.040 < 0.05, which means it has a positive influence on loyalty. Tariffs have a t value of 4.147 > 1.660 and sig 0.000 < 0.05, which means they have an influence on loyalty. Satisfaction has a t value of 3.969 > 1.660 and Sig. 0.000 < 0.05 which means satisfaction has a positive influence on loyalty. Service Quality, Rates and Satisfaction have a positive and significant influence on satisfaction with a calculated F value of 145.556 > F table 3.099 and 0.000 < 0.005. Satisfaction can be a mediator in the influence of Service Quality and Tariffs on Loyalty with a calculated t of 6.236 and a t table of 1.660 with a Sig value of 0.05, a mediation coefficient of 0.757419962768344. Satisfaction can be a mediator in the influence of tariffs on loyalty with a calculated t value of 3.226 and t table 1.660 with a Sig value. 0.05 and the mediation coefficient is 0.659383803